2001
DOI: 10.1016/s0001-2092(06)61744-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warming Therapy on Pressure Ulcers—a Randomized Trial

Abstract: Postoperative pressure ulcers are a common and expensive problem. Intraoperative hypothermia also is a common problem and may have a connection with impaired tissue viability. Researchers in this study hypothesized that intraoperative control of hypothermia may reduce the incidence of postoperative pressure ulcers. A randomized clinical trial (n = 338) was used to test the effects of using forced air warming therapy versus standard care. Results indicated an absolute risk reduction in pressure ulcers of 4.8% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 76 publications
(35 reference statements)
5
59
1
5
Order By: Relevance
“…Analysis of body mass index showed a significant difference (P ϭ.009) in outcome, with patients who developed pressure sores having a lower index than those who remained unaffected. 68 This finding is consistent with others' reports on low-weight individuals. 19,22 This may be related to the fact that patients with low body fat are less likely to maintain core temperature or that less body fat results in more bony prominences that require padding attention.…”
Section: Challenges Of Moisture and Immobilitysupporting
confidence: 92%
“…Analysis of body mass index showed a significant difference (P ϭ.009) in outcome, with patients who developed pressure sores having a lower index than those who remained unaffected. 68 This finding is consistent with others' reports on low-weight individuals. 19,22 This may be related to the fact that patients with low body fat are less likely to maintain core temperature or that less body fat results in more bony prominences that require padding attention.…”
Section: Challenges Of Moisture and Immobilitysupporting
confidence: 92%
“…Warming has been shown to be effective in preventing pressure sores [6] and in reducing infection after clean wound surgery [7,8]. Other studies have shown that warming enhances resistance to infection and controls bacterial numbers [9,10], but this is the first study to show that warming is effective in reducing MRSA colonization in human wounds.…”
Section: Discussionmentioning
confidence: 90%
“…Only one study, involving colorectal surgery (by definition clean-contaminated or contaminated), has demonstrated that FAW reduces the rate of SSI. 24,38,39 The authors of this study reported a three-fold reduction in SSI rates in patients who were warmed when compared to patients who were not warmed during surgery. 24 Whereas these researchers did use FAW to warm patients during surgery in the intervention group, a confounding factor was that they also used an average of 3 L of warmed fluid in the intervention group compared to the control group, in which fluid was not warmed.…”
Section: Benefits Of Avoiding Perioperative Hypothermiamentioning
confidence: 84%